Dielectric track detectors in fast neutron measurements and dosimetry. (November 2020) - Kwiatkowski, R.; Malinowska, A.; Szydlowski, A.; Dankowski, J.; Kurowski, A.; Gatarczyk, K.
Abstract: The main aim of the presented paper was to perform neutron measurements using Solid State Nuclear Track Detectors and to compare obtained results with those obtained on the basis of Monte Carlo simulations of the experimental setup. The CR-39 type track detectors coupled with various radiators were used to measure neutrons emitted from a DT neutron generator. The detectors were also shielded with various filters made of materials characterized by low cross sections for reactions with fast neutrons. The filters were used to block charged particles with energies lower than certain threshold. The track detectors after exposure to neutrons were etched in steps, and examined using an optical microscope equipped with automatic image acquisition system. The recorded images were analyzed using a specialized software. Based on the recorded track parameters, it is also possible to calculate linear energy transfer (LET) of the registered particles, and determine the radiation dose of the emitted neutrons. Highlights: Neutron emission from a neutron generator was investigated using PADC track detectors. Parameters of neutron emission were calculated on the basis of track parameters. Monte Carlo simulations were used to determine track detector response for neutrons.